THE EFFECT OF AUDIOVISUAL DISTRACTION ON THE ANXIETY OF PRESCHOOL AGE CHILDREN RECEIVING NEBULIZER THERAPY IN BHAYANGKARA BRIMOB HOSPITAL - Widari, Sylvia Elok; Risdiana, Rani (HEARTY, 2025)
Background: Anxiety felt during inhalation procedures can affect a child's psychosocial development and reduce the child's health status. The anxiety experienced by children who are given a nebulizer is indicated by signs and symptoms, namely the child becomes aggressive, angry, rebellious, does not know the staff and the hospital environment, which causes not all of the nebulizer medication given to be inhaled, thus affecting the dose of the drug and the healing process. Research Objective: To determine the effect of audiovisual distraction on anxiety in pre-school children who received nebulizer therapy at Bhayangkara Brimob Hospital Research Method: This research is quantitative research with the type of research used in this research being quasi experimental with a pre and post test research design without control group design. The research sample consisted of 62 respondents. The instrument in this research was to use a visual facial anxiety scale (VFAS) observation questionnaire sheet. Statistical analysis uses parametric analysis with Paired T-Test. Research Results: The average value of anxiety level before audiovisual distraction was 4.290 and after audiovisual distraction was 1.725. The results of the research revealed the value of Asymp. Sig. (2-tailed) of 0.000 is smaller than <0.05 Conclusions and Suggestions: There is an influence of audiovisual distraction on the anxiety of pre-school aged children who received nebulizer therapy at Bhayangkara Brimob Hospital. Suggestions for hospital management to add TV facilities by showing cartoon films or children's songs so that children feel happy and reduce anxiety during nebulizer therapy